Elmer Rice Redescoberto - Umaras, Regina Garkauskas (Palimpsesto - Revista do Programa de Pós-Graduação em Letras da UERJ, 2018)
Resenha JEW, Kimberly May. The theatrical experimentation of Elmer Rice. New York: New York University, 1998.